Protocol: Assessing the impact of interest‐holder engagement on guideline development: A systematic review - Lyubov Lytvyn; Jennifer Petkovic; Joanne Khabsa; Olivia Magwood; Pauline Campbell; Ian D. Graham; Kevin Pottie; Julia Bidonde; Heather Limburg; Danielle Pollock; Elie A. Akl; Thomas W. Concannon; et al. (Campbell Systematic Reviews)
Abstract This is the protocol for a Campbell systematic review. The objectives are as follows. The objective of this review is to identify and synthesize empirical research on the impacts of interest‐holder engagement on the guideline development process and content. Our research questions are as follows: (1) What are the empirical examples of impact on the process in health guideline development across any of the 18 steps of the GIN‐McMaster checklist? (2) What are the empirical examples of impact on the content in health guideline development across any of the 18 steps of the GIN‐McMaster checklist?